Gossypiboma- A rare case of breast fistula - Islam, B; Mortuza, MG; Ahmed, I; Alom, A (TAJ: Journal of Teachers Association, 2018)
Breast fistula is an uncommon disease usually occurs in young women. Most of the fistula is mammary duct fistula. Foreign body causing fistula in breast is very rare. Here a 50 years old female suddenly developed pain and swelling in her right breast, initially diagnosed as breast abscess and drained in a local clinic by a qualified surgeon, then the patient was improved but after 2 months another abscess was developed in opposite side of same breast which was burst spontaneously and fistulous tract formed and persist for 2 years. Then the patient was admitted in RMCH. FNAC report reveals granulomataous inflammation cytologically tuberculosis. Tubercular Chemotherapy was given for 2 months but no improvement. Finally surgery was decided, a retained surgical gauze (Gossypiboma) was found within the fistulous tract and fistulectomy was done and the wound laid open. Foreign body usually causes chronic discharging sinus but fistulous formation is very rare. TAJ 2016; 29(1): 58-60